Strategies Used in Translating Idioms in the Iron Man Movie - Mohammad Yahya; Mila Islami (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2019)
The strategies used by translators will have impact on transferring meaning of idioms. The strategies chosen may also have relatioship with the type of idioms.The theory of four strategies of translation has been used by a number researhers in their study about idiom translation. However, these four strategies cannot accomodate to identify all the strategies applied by the translators of the subtitle of Iron Man film. This study aims to identify the types of idioms in the Iron Man film and investigate the strategies applied by two translators, in the Indonesian subtitle in the film of the original CD by Marvel and that is from a website subscene.com. The identification of idioms in the film is based on the theory by Makkai (1972). While the categorization of the idioms is based on the theory by Fernando (1996). The theories proposed by Baker (1992) and Molina & Albir (2002) are used in analyzing the translation strategies of the idioms. The results shows there are 130 idioms classified into pure idioms (25%), semi idioms (23%) and literal idioms (51%). The most frequent strategy applied is paraphrasing both in the subtitle from the original CD by Marvel (77.6%) and from a website subscene.com (82.2%). Literal translations are also applied, showing the lack of translation competencies of the translators which potentially causes poor translation quality which resulted from the subtitling demand.